Accounting Principles - Hermanson, Roger H., Ph.D. CPA. (Irwin, 1992)
Accounting: The language of business, Processing accounting information, Assets and liabilities, Accounting theory and partnerships, Corporation Accounting, Analysis of financial statements, Product costing.